The Relationship Between Entrepreneurial Motivation and The Entrepreneurial Mental Attitude of Barber Training Participants at Dinas Koperasi and UMKM in Padang city - Mubarak, Afwan; Dasa Putri, Lili (Universitas Negeri Padang, 2024)
The low entrepreneurial mental attitude of barber trainees at Dinas Koperasi and UMKM in Padang City is the driving force behind this study. It is believed that this is because entrepreneurial motivation, as measured by factors like the need for achievement, risk-taking, self-confidence, strong desire, and creativity, is still lacking. This study intends to describe three things: (1) entrepreneurial motivation; (2) entrepreneurial mental attitude; and (3) the interaction between the two. The participants in the study are barber trainees from Dinas Koperasi and UMKM in Padang City. This study employs correlational research and a quantitative methodology. There were 45 responders in this study's population. Stratified random sampling is the method used for sampling. The sample was drawn from a thirty-person population. approaches to data analysis that make use of the product moment correlation formula and the percentage formula. The study's findings show that: (1) barber trainees at Padang City's Office of Cooperatives and MSMEs have low levels of entrepreneurial motivation; (2) these trainees' entrepreneurial mental attitudes are also low; and (3) there is a significant correlation between the trainees' entrepreneurial motivation and mental attitudes at Padang City's Dinas Koperasi and UMKM sites.Keywords: Entrepreneurial Motivation, Entrepreneurial Mental Attitude,Barber Training